The role of xylene as a nematicide formulation and its synergistic effects with abamectin in the management of pine wood nematodes - Min-Kyoung Kang; Hyeon-Ji Kim; Jong-Hoon Kim (Ecotoxicology and Environmental Safety)
Pine wilt disease (PWD), caused by the pine wood nematode, poses a significant global threat to forests, resulting in severe economic and environmental damage. Currently, managing the occurrence of PWD in plants remains an ongoing challenge due to its multiple modes of transmission and broad adaptability. Moreover, there are only a few nematicidal agents for controlling these harmful nematodes. Therefore, the identification of novel nematicidal agents has become urgent and is of critical practical and economic significance. This study aimed to evaluate xylene as a supplementary agent in managing pine wood nematodes. The nematicidal efficacy of xylene was assessed, revealing that it effectively suppresses the growth, reproduction, and behavior of Bursaphelenchus xylophilus at certain concentrations. Notably, the combination of xylene and abamectin achieved a 100 % mortality rate at a significantly lower concentration of 0.5 µg/mL, approximately eight times less than abamectin alone. In pot experiments, xylene treatment did not exhibit phytotoxicity towards pine trees, confirming its nematicidal activity. Furthermore, the xylene-abamectin combination effectively inhibited the development of PWD in 5-year-old Pinus densiflora trees at a dosage of 0.45 mg per tree, roughly 8 times lower than the required amount of abamectin alone under greenhouse conditions. This study is the first to demonstrate the nematicidal effects of xylene, suggesting that xylene could serve as an effective agent in nematode control formulations.